Adenosine Signaling Increases Proinflammatory and Profibrotic Mediators through Activation of a Functional Adenosine 2B Receptor in Renal Fibroblasts - Wilkinson, Patrick F; Farrell, Francis X; Morel, Diane; Law, William; Murphy, Suzanne (Annals of clinical and laboratory science, 2016)
Interstitial renal fibrosis is a major pathophysiological manifestation of patients diagnosed with Chronic Kidney Disease (CKD), Diabetic Nephropathy (DN) and other inflammatory diseases. Adenosine signaling is an innate autocrine and paracrine cellular signaling pathway involving several key mediators that are elevated in the blood and kidneys of patients with DN. In these studies, we hypothesized that extracellular adenosine signals through one or more functional adenosine GPCRs on renal fibroblasts which increases profibrotic and proinflammatory mediators by inducing an activated fibroblast phenotype. Utilizing the renal fibroblast cell line NRK-49F, the presence and relative abundance of adenosine receptors (AR) A1, A2A, A2B, and A3 were quantified by RT-PCR. Under normal homeostatic conditions, only AR1 and AR2B were detected. The functionality of each receptor was then assessed by receptor specific pharmacological agonism and antagonism and assessed for modulation of the GPCR associated secondary messenger molecule, cyclic adenosine monophosphate (cAMP). Agonism of the AR2B receptor resulted in increased intracellular cAMP while agonism of the AR1 receptor inhibited cAMP modulation. Upon direct agonism of the AR2B receptor, transcripts for profibrotic and inflammatory mediators including SMA-α, IL-6, TGF-β, CTGF, and fibronectin were elevated between 2-4 fold. These data indicate that renal fibroblasts express a functional AR1 receptor that inhibits cAMP upon stimulation, leading to a functional AR2B receptor that increases cAMP upon stimulation and also induces an activated fibroblast phenotype resulting in increased fibrotic and inflammatory mediators.